The Effect of Non-Physical Work Environment and Organizational Commitment on Turnover Intention Among Employees of PT. X in Surabaya - Alvina Marcelia; Mei Retno Adiwaty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to examine how the non-physical work environment and organizational commitment affect employee turnover at PT. X in Surabaya. In this study, a 1-5 Likert scale was used to measure the opinions, attitudes, and perceptions of individuals or groups regarding certain social phenomena. Responses to this scale could be positive or negative statements regarding an individual's attitude. The following study involved all 67 salesmen of PT. X in Surabaya. A saturated sample method was used to collect samples. SmartPLS 3 software was used to analyze the data after the questionnaire was distributed. The advantage of this software is that it requires a relatively small sample size compared to its competitors, and the bootstrapping method allows data to be distributed in a non-normal manner. The results of the study show that a good non-physical work environment and organizational commitment reduce employees' desire to leave PT. X in Surabaya. The following conclusion shows that a good non-physical work environment and high organizational commitment have a negative and significant effect on employees' desire to leave the company.